Leadership skills for women - Manning, Marilyn (Crisp Pub. Menlo ParkUS, 1995)
Provides information about the qualities that make people leaders, and teaches basic leadership skills that can be applied in the workplace. Addresses the unique challenges and opportunities women leaders face, but also presents the benefits of being a woman in leadership.